Rekonstruksi Vegetasi Pasca Kebakaran Di Blok Gunung Geulis,Suaka Margasatwa Cikepuh Berdasarkan Bukti-Bukti Palinologi - Tiffany Hanik Lestari; Winantris Winantris; Parikesit Parikesit (Pusat Survei Geologi, 2018)
The Gunung Geulis block, Cikepuh Wildlife Nature is one of the natural areas which is considered as the habitat for various wildlife. The area are currently degraded due to the fire. Reconstruction of the vegetation in Gunung Geulis block was conducted as an effort to understand the history of vegetation, so that in the future it can rehabilitate the burnt forest area through reforestation activities in accordance with the initial conditions of the habitat (before burning). This study used a transect method for soil sampling and acetolisys method to know the diversity of the sedimented sub-fossil pollen. Based on the results in the five sampling's points, the 90 types of both sub-fossil pollen and spores of plants (i.e., 34 types of sub-fossil pollens (arboreal pollen), 40 types of sub-fossil pollen (non-arboreal pollen), and 16 species of sub-fossil spores) were observed at five sampling points in Gunung Geulis block. This indicates that the annual fire intensity in the Gunung Geulis block were relatively high. Indeed, the correspoding block is undergoing a secondary succession. The vegetation changes that occur can be illustrated by the diversity of the observed sub-fossil pollen and spores in soil.Keyword : Pollen, Spores, Vegetation Reconstruction, Gunung Geulis, Cikepuh.